(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
In the global scientific literature, physiological changes in the visual system during pregnancy—such as reduced tear film stability and increased signs of dry eye, functional alterations in corneal sensitivity and thickness, transient shifts in refraction, decreased contact lens tolerance, and a physiological reduction in intraocular pressure—have been extensively documented. Likewise, pregnancy-associated pathological conditions—including hypertensive disorders, preeclampsia/eclampsia, posterior reversible encephalopathy syndrome (PRES), central serous chorioretinopathy, cranial neuropathies, progression of diabetic retinopathy, and other chorioretinal-neuro-ophthalmologic complications—have been thoroughly described.